Theology, hermeneutics, and imagination the crisis of interpretation at the end of modernity - Green, Garrett 1941- (Cambridge [u.a.] Cambridge University Press, 2000)
Preface; 1. Theological hermeneutics in the twilight of modernity; Part I. The Modern Roots of Suspicion; 2. The scandal of positivity: the Kantian paradigm in modern theology; 3. Against purism: Hamann's metacritique of Kant; 4. Feuerbach: forgotten father of the hermeneutics of suspicion; 5. Nietzschean suspicion and the Christian imagination; Part II. Christian Imagination in a Postmodern World: 6. The hermeneutics of difference: suspicion in postmodern guise; 7. The hermeneutic imperative: interpretation and the theological task; 8. The faithful imagination: suspicion and trust in a postmodern world; Appendix: Hamann's letter to Kraus; Bibliography; Index.
A revised and explanded version of the Edward Cadbury lectures delivered at the Univ. of Birmingham in Feb. and March 1998, under the title: The faithful imagination - Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Hermeneutics; Hermeneutics -- Religious aspects -- Christianity